(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical-methodological foundations of developing the knowledge of future physical education teachers about tourism and the system of developing the knowledge of future physical education teachers about sports tourism have been studied. Also, the conceptual bases of concepts related to sports tourism are analyzed.